2015
DOI: 10.5505/tjtes.2015.93236
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Traumatic Cerebrospinal Fluid Fistulas with Associated Lesions

Abstract: BACKGROUND:Head trauma is associated with a significant risk of cerebrospinal fluid (CSF) fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…They determined the duration of CLD based on the success of the system. Alagöz et al [17] reported 22 patients with traumatic CSF fistula and they performed conservative treatment or CLD in all patients before the surgical repair of the dural defect. In our series, post-traumatic CSF fistula was the cause of CLD in 15.55% of our patients, and the mean duration of CLD was 8.3 days (ranged between five and 12 days).…”
Section: Discussionmentioning
confidence: 99%
“…They determined the duration of CLD based on the success of the system. Alagöz et al [17] reported 22 patients with traumatic CSF fistula and they performed conservative treatment or CLD in all patients before the surgical repair of the dural defect. In our series, post-traumatic CSF fistula was the cause of CLD in 15.55% of our patients, and the mean duration of CLD was 8.3 days (ranged between five and 12 days).…”
Section: Discussionmentioning
confidence: 99%